Sosialisasi Pengenalan Huruf Hijaiyah Dengan Menggunakan Media Kartu Di TK Islam Al- Amanah - Wasalmi Wasalmi; Mutmainnah Mutmainnah; Nurulista Nurulista (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
Recognition and mastery of the hijaiyah letters, which are the basis for reading and studying the holy book Al-Qur'an from an early age, is very important, because if when reading the hijaiyah letters we are used to using the wrong words, it will give rise to different meanings so that we are required to read properly and correctly. The method for learning hijaiyyah letters is usually given by traditional (conventional) Koran teachers or people often call it the sequential method. With this method, children tend to be passive in receiving the Koran lessons, because the Koran teacher explains to the child how to learn to read the Hijaiyyah letters verbally and in body language. We carried out this socialization to introduce hijaiyah letters using card media at Al-amanah Islamic Kindergarten so that children are interested in learning and recognizing hijaiyah letters. The method we use is singing, asking questions and answers with students using cards that we have prepared which are useful for introducing hijaiyah letters easily and variedly and without vacuum. After conducting socialization, we saw that the children became more familiar with the hijaiyah letters and sang the hijaiyah letters with enthusiasm